Classificação psicoacústica do zumbido persistente - Suzuki, Flavia Alencar de Barros [UNIFESP] (2016)
Objective: To propose a new classification of persistent tinnitus using psychoacoustic characteristics and its association to the degree of discomfort, the impact on quality of life, the pitch, loudness and its masking. Method: A total of 110 adult patients of both genders treated at the Tinnitus Outpatient Clinic of UNIFESP according to the inclusion and exclusion criteria were included in the study. Patients underwent otorhinolaryngological, audiological, Pitch Matching and Loudness, Visual Analogue Scale (VAS), Tinnitus Handicap Inventory (THI) and Minimum Masking Level (MML) assessment. Results: A total of 181 complaints of tinnitus were identified in these 110 patients, being 93 (51%) Pure Tone (PT), and 88 (49%) Noise; 19 Low Pitch and 162 High Pitch; with a mean VAS score in PT of 5.47 and Noise of 6.66; mean PT Loudness of 12.31 dBSL and Noise of 10.51 dBSL. As for THI and MML, the 110 patients were separated into 3 groups with tinnitus, PT, Noise and multiple tinnitus (PT+Noise), with a mean THI being higher in the group with multiple tinnitus, of 61.38. For MML, we used White Noise (WN) and Narrow Band (NB) masking noise for high and low frequency. There were similarities between the groups with PT and multiple tinnitus. In the Noise group, different responses were found when using the NB at low frequency. Conclusion: In this psychoacoustic classification of tinnitus it was observed that: there is an association between the type of tinnitus perception and the sounds produced in the audiometer; the PT type showed higher loudness; the Noise type caused more discomfort; Multiple tinnitus is the one with a more severe effect on quality of life and less intensity is required for masking tinnitus when the pitch is similar to the masking noise used.